THE INCLUSIVE KINDERGARTEN IN THE PHILIPPINES: ACCESS AND AMPLE OPPORTUNITIES FOR EARLY LEARNERS WITH SPECIAL NEEDS (Proceedings of International Conference on Special Education, 2017)
The belief in education especially inclusive education has grown. Inclusive education nowadays is very essential specifically for diverse students who have learning needs and it is also the basis for a more unbiased society. An evaluation on how inclusive kindergarten schools implemented the inclusion of early learners with disabilities was the objective of this study. Specifically, it determined the current status on the level of implementation of inclusive education practices; evaluated the extent of attainment of the program toward achieving specific goals to expand inclusive education; recognized best practices observed in the implementation of inclusive kindergarten education program and identified the challenges met by the respondents; This research work employed the descriptive evaluative design as well as qualitative type were used to determine the challenges experienced and best practices observed in the implementation of an inclusive kindergarten program through a focus group discussion with the principals and teachers. Results showed that the level of school implementation of inclusive kindergarten program is generally observed to be very high; attainment of the program objectives/outcomes consistently yielded a high level of implementation with approximately 61%-80% target indicators implemented in one of the City School Divisions in Southern Philippines; best practices include dedication of teachers to teaching children with special needs, appropriate school environment, inservice trainings conducted to teachers handling children with special needs, curriculum modification and support of parents to inclusive education programs, while challenges met consisted of attitude of teachers towards inclusive education, workload of teachers, acceptance of parents having children with special needs, assessment and strategies in handling children with behavioral problem. Hence, the study concluded that inclusive education in one of the City School Divisions in Southern Philippines is highly implemented.